1997
DOI: 10.1111/j.1365-2710.1997.tb00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the disposition kinetics of lidocaine and ± prilocaine in 20 patients undergoing intravenous regional anaesthesia during day case surgery

Abstract: Results:The mean onset time of surgical analgesia of lidocaine was 11-2 ± 5*1 min and that of prilo caine was 10*9 ± 6 * 0 min. After releasing the tourniquet, lidocaine is bi-exponentially elim i nated with a tlj2a of 4*3 ± 2*1 min and a tlf2/} of 79*1 ± 31*2 min. Total body clearance was 0*86 dt 0*39 litres/min. Prilocaine is rapidly and bi-exponentially eliminated with a of 3*0 ± 1*6 min and a tll2^ o f 29-9 ± 1 5 * 7 min. The total body clearance of prilocaine is higher than that of lidocaine, 4*15 ± 1-31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…In addition, very few or no reports were attributed to lidocaine. Other followup studies have observed similar results [22][23][24][25][26]. So, it was suggested that an important cause of paresthesia could be related to the local anesthetic dosedependent neurotoxicity.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, very few or no reports were attributed to lidocaine. Other followup studies have observed similar results [22][23][24][25][26]. So, it was suggested that an important cause of paresthesia could be related to the local anesthetic dosedependent neurotoxicity.…”
Section: Discussionsupporting
confidence: 65%
“…This local anesthetic of frequent use in dentistry is now slowly entering other fields (Van Oss et al 1989;Simon et al 1998). Carticaine was reported to be administered in over 37% of dental anesthesias in Canada (Haas and Lennon 1995) and 90% in Germany (Daublander et al 1997), and it is also widely used in Italy and The Netherlands (Oertel et al 1997).…”
Section: Introductionmentioning
confidence: 97%
“…12 Following infusion into the abdominal area and the hips, saturation of the esterases can be assumed, but not for infusion under the chin. Low systemic concentrations and rapid metabolization of articaine HCl also have been observed in a study comparing the effects of articaine and lidocaine in intravenous regional anesthesia, 18 in which large amounts of the drug are infused into the blood-drained extremities.…”
Section: Discussionmentioning
confidence: 76%